2009
DOI: 10.1073/pnas.0901652106
|View full text |Cite
|
Sign up to set email alerts
|

The niche, limits to species' distributions, and spatiotemporal variation in demography across the elevation ranges of two monkeyflowers

Abstract: Understanding the processes that create and maintain species' geographic range limits has implications for many questions in ecology, evolution, and conservation biology. Many expectations for the ecological and evolutionary dynamics of populations at the range margin rest on the concordance of geographic limits and the limits of a species' ecological niche. If range limits are coincident with niche limits, then marginal populations should have lower and/or more variable vital rates and population growth rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
110
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 52 publications
(59 reference statements)
3
110
3
1
Order By: Relevance
“…For the purpose of this paper, we use the term in its Grinnellian sense (Jackson and Overpeck 2000;Soberón 2007): niches are subsets of a multivariate space of environmental conditions defined in terms of variables that are not consumed or affected (at least in ecologically relevant timespans) by the presence of the species in question within which the species can maintain populations without inmigrational subsidy. The relationships between these environmental subsets and geography are complex, and frequently do not correspond to expected patterns (Angert 2009); as a result, it is necessary to understand the caveats associated with deriving niche estimates from species' occurrences across realized distributions.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this paper, we use the term in its Grinnellian sense (Jackson and Overpeck 2000;Soberón 2007): niches are subsets of a multivariate space of environmental conditions defined in terms of variables that are not consumed or affected (at least in ecologically relevant timespans) by the presence of the species in question within which the species can maintain populations without inmigrational subsidy. The relationships between these environmental subsets and geography are complex, and frequently do not correspond to expected patterns (Angert 2009); as a result, it is necessary to understand the caveats associated with deriving niche estimates from species' occurrences across realized distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not known whether these effects operate over elevational gradients, conspecific densities (and thus their frequency relative to heterospecifics) are known to respond to abiotic factors that change with elevation ( Fig. 1D) and at (elevational) range centres versus range margins (Angert 2009). For example, a recent study using data from 16 alpine experiments found evidence for positive plant-plant interactions at high elevations (facilitation) versus negative plant-plant interactions (competition) at low elevation, where both of these dynamics were driven by environmental stress and neighbour trait effects (Michalet et al 2014).…”
Section: Plant-plant Interactions Influence Plant Traits and Insect Hmentioning
confidence: 99%
“…Therefore, how populations of a given species are affected by climate change along the species range is still unclear. Yet, the populations of a given species are not experiencing similar environmental conditions and are not similarly adapted to environmental changes within the species range (Holt 2003;Both & te Marvelde 2007;Angert 2009;Both et al 2010). Consequently, following climate change, population dynamics of a given species could vary across the species range rather than being uniformly distributed.…”
Section: Introductionmentioning
confidence: 99%